Taxonomy of the Marine Genus Thalassodrilides (Oligochaeta:Tubificidae) - Erséus, C. (Transactions of the American Microscopical Society, 1981)
The brackish-water genus Thalassodrilides is taxonomically revised to include two clear species, Limnodriloides gurwitschi and Thalassodrilus belli, whereas Thalassodrilides milleri is retained in the genus as a species incertae sedis. Curacaodrilus is considered a junior synonym for Thalassodrilides, and Curacaodrilus sinus a junior synonym for T. gurwitschi. The species of Thalassodrilides are characterized by: (1) their possession of a barrel-shaped, thick-walled section of the esophagus in segment IX; (2) their simple atria with small lobes of broadly attached prostate glands; and (3) their muscular, elaborate eversible pseudopenes.